Quality Management Enhances Competitiveness and Market Share of BRI Savings - Arief Wibowo; Yulizar Verda Febrianto; Farida Indriani (Arthatama: Journal of Business Management and Accounting, 2025)
In the context of intensifying competition within the Indonesian banking sector in Bank Rakyat Indonesia (BRI) is challenged to sustain its relevance and competitive advantage. This study is investigates the strategic of quality management in enhancing the market position of BRI’s savings products (case study of BRI Jakarta 1 Regional Office). Employing a qualitative research approach through a case study method, data were gathered via in-depth interviews, non-participant observations, document analysis, and focus group discussions with key stakeholders, including regional management, employees, and selected customers of BRI. The study is grounded in the theoretical framework of Total Quality Management (TQM). These improvements collectively reinforce BRI’s competitive positioning in the savings market. Furthermore, enhancements in customer experience and service responsiveness contribute positively to the expansion of market share, despite persistent competitive pressures from leading private banks such as BCA and emerging fintech platforms. The study concludes that quality management serves as a critical strategic enabler for market share growth in the savings segment. Policy recommendations include the acceleration of digital transformation initiatives, upskilling of human resources, and the institutionalization of customer satisfaction monitoring mechanisms as part of a long-term quality strategy.